Theory and history of folklore - Propp, V. I͡A. (Vladimir I͡Akovlevich) 1895-1970 (Theory and history of literature, 1984)
"This book will give Propp's admirers in the English-speaking world a whole new perspective on this distinguished scholar's contribution to folkloristics. Liberman provides the necessary background in terms of Russian/Soviet intellectual (and political) currents to place Propp's work in a new light. No student of structuralism in folklore can afford to miss Liberman's anthology."--Alan Dundes (from cover)